Aumento da seletividade de cultivares de trigo ao S-metolacloro com o uso de protetores - Schaeffer, Otávio Augusto (2024)
Weed resistance limits the mechanisms of action that can be used in chemical control. Ryegrass (Lolium perenne spp. multiflorum Lam.) is one of the main weeds of winter crops in southern Brazil, mainly in wheat (Triticum aestivum). The existence of resistant biotypes of the species makes the adoption of different practices a vital tool for managing the weed. The use of preemergent herbicides allows new strategies for managing this weed. In this sense, S-metolachlor stands out for its ability to control broadleaf weeds and grasses. On the other hand, the use of herbicide can cause injuries to the wheat crop, making initial establishment difficult. One of the ways to contain this damage is the use of protectors transmitted through seed treatment, and the selection of more tolerant cultivars. In some cases, these protective molecules can cause phytotoxicity in the seeds, interfering with the morphophysiology of the plants and consequently reducing productivity. Thus, the study aimed to search for additive strategies for the tolerance of wheat crops to the herbicide S-metolachlor and to observe the selectivity of protectors used in the treatment of stored seeds. Therefore, three studies were carried out, the first of which aimed to evaluate the necessary doses of two protectants (fluxfenim and metcamifem) in order to mitigate the damage caused by S-metolachlor in the pre-emergence of the wheat cultivar Tbio Toruk. In the second study, the objective was to evaluate the tolerance of three wheat cultivars (ORS Senna, Tbio Audaz and Tbio Toruk) to doses of S-metolachlor applied pre-emergence. And finally, the third experiment proposed the evaluation of the impact of treating wheat seeds with fluxfenim in different storage periods on physiological parameters. Fluxfenim was able to reduce the injuries caused by S-metolachlor to wheat crops, at a dose of 0.096 g.kg-1. Metcamifem, within the dose spectrum tested (0 to 8 g.kg-1), was not able to reduce the phytotoxicity caused by the herbicide. The ORS Senna cultivar has greater tolerance to the herbicide S-metolachlor, compared to TBIO Audaz and TBIO Toruk. The presence of fluxfenim at a dose of 0.096 g.kg-1 in treated seeds did not negatively influence physiological parameters within 120 days of storage. In conclusion, fluxfenim is effective in reducing the phytotoxicity exerted by S-metolachlor on wheat crops. Conversely, metcamifem is ineffective in reducing this damage. The wheat cultivar ORS Senna has greater tolerance to the herbicide S-metolachlor, when compared to Tbio Audaz and Tbio Toruk. Fluxofenim at a dose of 0.096 g.Kg-1 of seeds is selective, not resulting in reductions in the physiological parameters of seeds even when stored within 120 days.